HUBUNGAN PENGETAHUAN, SIKAP REMAJA DAN PERAN PETUGAS KESEHATAN DENGAN KEPATUHAN KONSUMSI TABLET FE PADA REMAJA PUTRI DI POSYANDU REMAJA SEHATI DESA ALUE GENTENG KECAMATAN RANTO PEUREULAK KABUPATEN ACEH TIMUR - Armiatin (Jurnal Cakrawala Ilmiah, 2023)
Background: The prevalence of anemia in the world is very high, especially in developing countries including Indonesia. The impact of anemia seen in adolescents is stunted growth, the body is easily infected, reduced body fitness, decreased enthusiasm for learning and achievement Research : For knowing the relationship between knowledge and attitudes with adherence to fe tablet consumption in young women and the role of health workers at the Sehati Youth Posyandu, Alue Genteng Village, Ranto Peureulak District, East Aceh Regency in 2022 . Research design : research analytic with approach cross sectional . Population whole teenager daughter in the Working Area Integrated Healthcare Center Teenager Healthy Village Alue Rooftile Subdistrict Ranto Peureulak East Aceh district , totaling 127 youth daughter . The sampling technique in this study was purposive sampling , namely the research focused on 56 young women. Results Research : There is a relationship between knowledge and adherence to Fe tablet consumption where p-value = 0.0 05. There is a relationship attitude with adherence to consumption of fe tablets where p-value = 0.0 00. There is no relationship the role of officers with fe tablet consumption adherence where p-value = 0.925 . Suggestion : Expected to officer health so you can more socialize activity with counseling or education health Public specifically about benefit fe to teenager still daughter _ have knowledge not enough and motivating teenager already daughter _ knowledgeable good to obey in taking Fe tablets .